Library Instruction in Communication Disorders: Which Databases Should Be Prioritized? - Adelia Grabowsky (Issues in Science and Technology Librarianship)
The field of communication disorders encompasses the health science disciplines of both speech-language pathology and audiology. Pertinent literature for communication disorders can be found in a number of databases. Librarians providing information literacy instruction may not have the time to cover more than a few resources. This study develops a list of commonly recommended databases and a list of core journals in communication disorders and then looks at indexing of the journals to discover which databases should be prioritized in library sessions. [ABSTRACT FROM AUTHOR]